Antibiotic repeat prescriptions: are patients not re-filling them properly? - Zayegh, Iman; Charrois, Theresa; Hughes, Jeff; Hoti, Kreshnik (BioMed Central Ltd., 2014)
Objective: This study aimed to explore patients’ utilization of repeat prescriptions for antibiotics indicated in upper respiratory tract infections (URTI). An emphasis was placed on whether the current system of repeat prescriptions contributes to patients self-diagnosing infections and if so, identify the common reasons for this. Methods: This is a prospective study of self-reported use of repeat antibiotic prescriptions by pharmacy consumers presenting with repeat prescriptions for antibiotics commonly indicated in URTIs. Data were collected via self-completed surveys in Perth metropolitan pharmacies. Results: A total of 123 respondents participated in this study from 19 Perth metropolitan pharmacies. Of the respondents, approximately a third of them (33.9%) presented to the pharmacy to fill their antibiotic repeat prescription one month or more from the time the original prescription was written (i.e. time when original diagnosis was made by a doctor). Over two thirds of respondents indicated to not have consulted their doctor prior to presenting to the pharmacy to have their antibiotic repeat prescription dispensed (i.e. 68.3%). The most common reasons for this were that their ‘doctor had told them to take the second course’ (38%), followed by potential self-diagnosis (29%), i.e. ‘they had the same symptoms as the last time they took the antibiotics’. Approximately one third (33.1%) of respondents indicated they ‘were not told what the repeat prescription was needed for’ when they were originally prescribed the antibiotic. Respondents who presented to fill their repeat prescription more than 2 weeks after the original prescription written were more likely not have consulted their doctor (p = 0.006, 95% CI [1.16, 2.01]) and not to know why their repeat was needed (p = 0.010, 95% CI [1.07,2.18]).Conclusions: Findings of this study suggested that the current 12 month validity of antibiotics repeat prescriptions is potentially contributing to patients’ self-diagnosis of URTIs and therefore potential misuse of antibiotics. This may be contributing to the rise of antimicrobial resistance. The study also outlines some common reasons for patients potentially self-diagnosing URTIs when using repeat prescriptions. Larger Australian studies are needed to confirm these findings.